2022
DOI: 10.1049/stg2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation methods for dispatch and control of energy storage with renewable integration

Abstract: Renewable energy integration is an effective measure to resolve environmental problems and implement sustainable development, yet the volatility of wind and solar generation has a profound impact on power system operation, calling for sufficient backup capacity. Energy storage can shift demand over time and mitigate real‐time power mismatch and thus help integrate renewable energy resources into power grids. However, the unit capacity price of energy storage is still relatively high, and the capacity of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…This represents the percentage of each participating generator owned by the examined generator. The O row vector can be understood as the counterpart of the p vector in Equation (5).…”
Section: Formulation Of Single Case Quadratic Programming Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents the percentage of each participating generator owned by the examined generator. The O row vector can be understood as the counterpart of the p vector in Equation (5).…”
Section: Formulation Of Single Case Quadratic Programming Problemmentioning
confidence: 99%
“…Such RES generation methods offer environmental and sustainability benefits [5]. However, their production is notably volatile, owing to dependence on fluctuating weather patterns [5,6]. This results in high levels of variance in generator revenue.…”
Section: Introductionmentioning
confidence: 99%
“…The scheduling of energy storage is a typical multi-stage decision process. In the real application, it is found that nonanticipativity and multi-stage robustness should be considered for multi-stage scheduling problems in recent years and relevant literatures have given some examples to illustrate the serious consequences if these two requirements are not satisfied [8] - [10]. To better explain the two concepts, we note that there is a salient feature in the multi-stage scheduling process that makes the problem completely different from the traditional deterministic optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Load frequency control is one of the essential applications of automatic generation control. However, the structure of the power system is becoming increasingly complex with new energy grid connections and the requirements for security and reliability of power systems are increasing [7][8][9]. Meanwhile, due to its reliance on modern network and communication technology, LFC is exposed to cyber attacks, like denial-of-service (DoS) attacks and deception attack, which will interfere with the control centre's directives for adjustment and could result in severe grid mishaps [10][11][12].…”
mentioning
confidence: 99%